Atividade de ectoenzimas e de colinesterases e biomarcadores de estresse oxidativo em pacientes com câncer de pulmão - Zanini, Daniela (2012)
Lung cancer has become one of the most commonly diagnosed neoplastic diseases, as well as one of the most lethal worldwide, characterized, therefore, as a public health problem. This spread of lung cancer in the world population, which is clearly seen in statistics, is closely related to smoking, and smoking is considered one of the main risk factors that lead to the development of cancer since the year 1950. Research has also shown that there is a close relationship between cigarette consumption, the emergence of events pro-inflammatory and immunosuppressive and the development of lung cancer. In this context, it is important to study enzyme nucleotide triphosphate diphosphohydrolase (NTPDase), adenosine deaminase (ADA) and acetylcholinesterase (AChE), which are involved in the control of inflammatory processes and in the regulation of immunological events, and changes in their activities have been observed in several diseases, including cancer. Studies reveal that oxidative stress is closely associated with the development and progression of cancer, being extremely important to evaluate these aspects of cellular functions in a group of patients with lung cancer. The objective of this study was to investigate the activity of NTPDase and its expression (CD39) in lymphocytes, ADA and butyrylcholinesterase (BChE) in serum, AChE, superoxide dismutase (SOD) and catalase (CAT) in whole blood and the content of protein thiols (T-SH) and non-protein thiols (NPSH) in the serum of 31 patients with lung cancer, non small cell, treated at the Hematology/Oncology, University Hospital of Santa Maria. The results showed a significant increase in NTPDase activity for both, hydrolysis of ATP and ADP, in lymphocytes of patients with lung cancer. These results suggest that the pro-inflammatory effects triggered by the ATP in the extracellular environment may be reduced in these patients. However there was an increase of ADA activity in serum of patients with lung cancer when compared with the control group, a fact that promotes a drop in levels of extracellular adenosine. Thus, it is known that adenosine has anti-inflammatory properties, this increase of ADA activity could be providing an exacerbation of pro-inflammatory events in targeted patients in the study. Another important finding was the increase of AChE activity in whole blood in patients with lung cancer, compared with the control group. This likely reduced levels of acetylcholine (ACh) in blood also cause a decrease in anti-inflammatory activity characteristic of this molecule. Already, as the activity of SOD and CAT as well as the levels of T-SH and NPSH, all showed superior results in patients with lung cancer when compared with the control group. Thus, it is evident that thiol compounds may be acting in detoxification reactions and protecting these patients. Therefore, the results reported here suggest that lung cancer has a significant change in the enzyme activity of purinergic and cholinergic systems involved in inflammatory processes, and the oxidative profile in these patients, and the parameters mentioned in this research be useful in clinical medicine, to monitor the disease.